Effect of Turmeric Oil in Chitosan-Based Edible Coating on Physical and Chemical Properties of Strawberry - binti Mohd Yusof, Noorsuhana; binti Jai, Junaidah; Ain binti Zulkiflee, Nurul; Fatin Alia binti Mustapha, Nurul; Iranati binti Md. Sharif, Zatul (International Journal of Engineering and Technology, 2018)
Foodborne outbreaks, precocious decaying and economic losses are common problems related to fresh fruit retention. These problems have led to the advance of novel technologies and systems for food protection such as edible coating based on natural source materials. In this study, a chitosan based edible coating had been applied on the surface of strawberry to lengthen its shelf-life. It also offers protection against bacterial infection that leads to strawberry spoilage by supressing respiration, transpiration and microbial growth. Turmeric essential oil was added in the chitosan coating as innovation based on the possible synergy effect of these two components to improve the storability of strawberries after postharvest which is a crucial point for import-export of fresh fruits. The objective of this study was to determine the effect of chitosan-based edible coating with turmeric essential oil as bioactive ingredient on chemical and physical properties of strawberry. The chitosan-based edible coating was added with different concentrations of turmeric oil 0%, 5%, 10% and 20% while uncoated strawberry was named as control. Visual decay infection, structural analysis of chitosan-based solution, vitamin C determination and total soluble solid content (TSS) were then investigated. The results indicated that coated strawberry with presence of turmeric oil were able to maintain the studied chemical and physical properties of strawberries during 7 days of storage more efficiently than control and 0% concentration of turmeric oil. Study also found that the strawberry that contains highest concentration of turmeric oil at 20% had the lowest percentage of visual decay (<10%), the lowest total soluble solid solid content (3.6%) and the highest content of ascorbic acid (0.73 mg100g-1). Therefore, the synergy between chitosan-based edible coating with turmeric oil successfully improved the longevity shelf-life by extending the postharvest deterioration of strawberries.Â